Saccharification Of Palm Oil Mill Effluent Solid And Oil Palm Fruit Fiber To Fermentable Sugars For Acetone-Butanol-Ethanol Fermentation - Khaw, Teik Seong (2001)
The effect of chemical pretreatments on saccharification of palm oil mill effluent (POME) solid and 'oil palm fruit fiber (OPFF) was investigated. Among the chemical pretreatments applied to the substrate (NaOH 0.5%, Nth 0.5%, HCI 0.5%, HN03 0.5% and EDTA 0.5%), the OPFF treated with 0.5% NaOH gave the highest production of fermentable sugars. However, the saccharification performance for chemically treated POME solid was not significantly different as compared to untreated POME solid. The used of autoclaved OPFF at 121 oC, 15 psi with NaOH for 5 minute, increased the degree of hydrolysis up to 46% as compared to untreated OPFF. The optimum concentration of NaOH for the treatment of OPFF was 2%. The improvement in hydrolysis of OPFF was related to an increase of cellulose content, and a decrease in hemicellulose and lignin content.